BECOMING OF SUBJECT FIELD OF CONTEMPORARY VISUAL STUDIES - A. M. Tormakhova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the work is to analyze the trends of contemporary visual studies that represent a combination of visual presentations of social and cultural communities and traditions. The task is to make an attempt to highlight main theories leading authors to create a coherent system of concepts related to the field of visual studies. The methodology involves an appeal to the philosophical, cultural, cultural-anthropological concepts that define the specificity of contemporary visual studies. The works of Western scholars like P. Bourdieu, U. Eco, U. Mitchell, N. Mirzoeff, S. Pink, G. Rose, J. Rubi, P. Shtompka, N. Underberg, E. Zorn are also involved. In the article presented the theory of A. Usmanova and S. Avanesov. Originality lies in the creation of a single integrated approach to the visual review. There were clarified the concepts that form the basis of visual studies: visual culture, visual turn and visual practice. The results can be used for the training course "Visual practices and communication." The conclusions indicated that the study of practical areas, including the study of the phenomenon of fashion, the visual design of the city, cinema and photography, advertising and television is important, both in the west and in the national philosophy. Perceptions and practices of various forms of visual presentation serve as communication. They pointed out that the study provides a visual environment to attract a large array of material, which is typically analyzed within disciplines philosophical, cultural and anthropological circles. Using an interdisciplinary approach will contribute to the development of a single methodology, which can be involved in the analysis of all phenomena of visual culture.